Positive pole piece, battery and electric equipment
By designing a gradient structure in the positive electrode active material layer, the problem of increasing penetration difficulty of electrolyte is solved and the rate performance is improved.
Patent Information
- Application Number
- CN202310979770.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-04
AI Technical Summary
As the thickness of the positive electrode active material layer increases, the penetration difficulty of electrolyte becomes greater, affecting the rate performance.
By designing a gradient structure in the positive electrode active material layer, the tortuosity on the outside is greater than the tortuosity on the inside, the seepage performance on the inside is improved and the electrolyte is infiltrated from the outside to the inside.
The electrolyte infiltration performance and liquid absorption rate of the positive electrode active material layer are improved, and the rate performance is enhanced.
Smart Images

Figure CN119447183A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] As the requirements for energy density increase, some technical solutions have proposed the preparation of thick electrodes, that is, increasing the thickness of the active material layer. The electrolyte wetting performance of the positive electrode sheet is a factor affecting battery performance. However, as the thickness of the positive electrode active material layer increases, it becomes more difficult for the electrolyte to penetrate the positive electrode active material layer, and the rate performance is easily affected due to incomplete electrolyte wetting. Summary of the invention
[0003] In view of the above problems, the present application provides a positive electrode plate, a battery and an electrical device, which can improve the electrolyte wetting performance of the positive electrode active material layer, thereby facilitating the improvement of rate performance.
[0004] The embodiment of the present application is implemented as follows:
[0005] In a first aspect, an embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active material layer, the positive electrode current collector and the positive electrode active material layer are distributed along the thickness direction of the positive electrode sheet; wherein, in a plurality of designated areas at different positions of the positive electrode active material layer, along the thickness direction of the positive electrode sheet, 50 μm ≤ the thickness of the designated area < the thickness of the positive electrode active material layer, satisfying: in two designated areas distributed along the thickness direction of the positive electrode sheet, the tortuosity of the designated area on the side away from the positive electrode current collector is T 外 , the tortuosity of the designated area close to the positive electrode current collector is T 内 , T 外 >T 内 .
[0006] In the technical solution of the embodiment of the present application, relative to the position of the positive electrode current collector, the tortuosity of the outer designated area is greater than the tortuosity of the inner designated area, so that the inner designated area has better seepage performance, which is beneficial for the electrolyte to infiltrate the positive electrode active material layer from the outside to the inside, and can increase the liquid absorption rate and liquid absorption amount of the positive electrode active material layer, thereby improving the electrolyte infiltration performance of the positive electrode active material layer, which is beneficial to improving the rate performance.
[0007] In some embodiments, T 外 / T 内 =1.07~1.24; Optionally, T 外 / T 内 =1.09~1.17; Optionally, T 外 / T 内 =1.09~1.16.
[0008] In these embodiments, relative to the position of the positive electrode current collector, the outside and the inside maintain a certain tortuosity ratio, and the permeability performance of the specified area of the inside relative to the outside is improved to a certain extent, which is conducive to better infiltration of the electrolyte into the positive electrode active material layer from the outside to the inside.
[0009] In some embodiments, at least one of the following conditions (a1) to (a3) is satisfied: (a1) the tortuosity of the designated area at the first position is T 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 1.60≤T 表 ≤2.05; optionally, 1.70≤T 表 ≤1.75; (a2) the tortuosity of the designated area at the second position is T 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 1.50≤T 中 ≤1.65; optionally, 1.50≤T 中 ≤1.55; (a3) The tortuosity of the designated area at the third position is T 底 , the third position is located on the side of the positive electrode active material layer close to the positive electrode current collector; 1.30≤T 底 ≤1.55; optionally, 1.30≤T 底 ≤1.35.
[0010] In these embodiments, the surface, middle and bottom of the positive electrode active material layer have a smaller tortuosity, which is conducive to faster infiltration of the electrolyte into the surface, middle and bottom of the positive electrode active material layer; the tortuosity of the surface, middle and bottom of the positive electrode active material layer gradually decreases with a suitable gradient, which is conducive to better infiltration of the electrolyte into the positive electrode active material layer from the outside to the inside.
[0011] In some embodiments, the tortuosity of the entire positive electrode active material layer is T 总 , 1.45≤T 总 ≤1.75; optionally, 1.50≤T 总 ≤1.70.
[0012] In these embodiments, the positive electrode active material layer has a smaller tortuosity as a whole. The tortuosity close to 1 indicates that the transmission channel in the positive electrode active material layer extends in a direction close to the thickness of the positive electrode sheet, which is conducive to faster infiltration of the electrolyte in the positive electrode active material layer as a whole.
[0013] In some embodiments, the positive electrode active material layer includes a positive electrode active material; in two designated areas distributed along the thickness direction of the positive electrode sheet, the mass proportion of the positive electrode active material in the designated area on the side away from the positive electrode current collector is C1 外, the mass proportion of the positive electrode active material in the designated area close to the positive electrode current collector is C1 内 , C1 外 -C1 内 =0.1%~1.2%; Optionally, C1 外 -C1 内 =0.1%~1.0%.
[0014] In these embodiments, C1 外 Higher than C1 内 A certain range is conducive to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer from the outside to the inside.
[0015] In some embodiments, at least one of the following conditions (b1) to (b3) is satisfied: (b1) The mass ratio of the positive electrode active material in the designated area at the first position is C1 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 97.4% ≤ C1 表 ≤98.1%; optionally, 97.4%≤C1 表 ≤98.0%; (b2) The mass proportion of the positive electrode active material in the designated area located at the second position is C1 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 96.7% ≤ C1 中 ≤97.3%; optionally, 97.1%≤C1 中 ≤97.2%; (b3) The mass proportion of the positive electrode active material in the designated area located at the third position is C1 底 , the third position is located on the side of the positive electrode active material layer close to the positive electrode current collector; 95.9% ≤ C1 底 ≤96.9%; optionally, 96.4%≤C1 底 ≤96.6%.
[0016] In these embodiments, the surface, middle and bottom of the positive electrode active material layer have a larger positive electrode active material mass ratio, which is conducive to providing a higher energy density; the positive electrode active material mass ratio of the surface, middle and bottom of the positive electrode active material layer gradually decreases with a suitable gradient, which is conducive to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to better infiltration of the electrolyte into the positive electrode active material layer from the outside to the inside.
[0017] In some embodiments, the positive electrode active material layer includes a binder; in two designated areas distributed along the thickness direction of the positive electrode sheet, the binder mass ratio in the designated area on the side away from the positive electrode current collector is C2外 The mass ratio of the binder in the designated area close to the positive electrode current collector is C2 内 , C2 内 -C2 外 =0.05%~0.8%; Optionally, C2 内 -C2 外 =0.05%~0.45%.
[0018] In these embodiments, C2 外 Lower than C2 内 A certain range is conducive to regulating C1 外 Higher than C1 内 A certain range, which is conducive to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer from the outside to the inside.
[0019] In some embodiments, at least one of the following conditions (c1) to (c3) is satisfied: (c1) the mass proportion of the binder in the designated area at the first position is C2 表 , the first position is located in the positive electrode active material layer away from the positive electrode current collector, 0.5% ≤ C2 表 ≤1.0%; optionally, 0.6%≤C2 表 ≤0.9%; (c2) The mass proportion of the binder in the designated area at the second position is C2 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 1.0% ≤ C2 中 ≤1.3%; optionally, 1.0%≤C2 中 ≤1.1%; (c3) The mass proportion of the binder in the designated area at the third position is C2 底 , the third position is located on the side of the positive electrode active material layer close to the positive electrode current collector; 1.3% ≤ C2 底 ≤1.8%; optionally, 1.5%≤C2 底 ≤1.8%; optionally, 1.5%≤C2 底 ≤1.7%.
[0020] In these embodiments, the surface, middle and bottom of the positive electrode active material layer have a suitable binder mass ratio, which is conducive to providing better bonding performance; the binder mass ratio of the surface, middle and bottom of the positive electrode active material layer gradually increases with a suitable gradient, which is conducive to regulating C1 表 、C1 中 、C1 底 Gradually decreasing with a suitable gradient is beneficial to regulating T 表 , T 中 , T 底Gradually decreasing with a suitable gradient is conducive to better infiltration of the electrolyte into the positive electrode active material layer from the outside to the inside, and is also conducive to improving the overall structural stability of the positive electrode active material layer.
[0021] In some embodiments, the positive electrode active material layer includes a conductive agent; in two designated areas distributed along the thickness direction of the positive electrode sheet, the conductive agent mass ratio in the designated area on the side away from the positive electrode current collector is C3 外 The mass proportion of the conductive agent in the designated area close to the positive electrode current collector is C3 内 , C3 内 -C3 外 =0.2%~0.8%; Optionally, C3 内 -C3 外 =0.2%~0.45%.
[0022] In these embodiments, C3 外 Lower than C3 内 A certain range is conducive to regulating C1 外 Higher than C1 内 A certain range, which is conducive to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer from the outside to the inside.
[0023] In some embodiments, at least one of the following conditions (c1) to (c3) is satisfied: (c1) the mass proportion of the conductive agent in the designated area at the first position is C3 表 , the first position is located in the positive electrode active material layer away from the positive electrode current collector, 0.7% ≤ C3 表 ≤1.4%; optionally, 0.9%≤C3 表 ≤1.4%; optionally, 0.9%≤C3 表 ≤1.2%; (c2) The mass proportion of the conductive agent in the designated area at the second position is C3 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 1.1% ≤ C3 中 ≤1.7%; optionally, 1.2%≤C3 中 ≤1.7%; optionally, 1.2%≤C3 中 ≤1.3%; (c3) The mass proportion of the conductive agent in the designated area at the third position is C3 底 , the third position is located on the side of the positive electrode active material layer close to the positive electrode current collector; 1.2% ≤ C3 底 ≤2.0%; optionally, 1.5%≤C3 底 ≤2.0%; optionally, 1.5%≤C3 底 ≤1.7%.
[0024] In these embodiments, the surface, middle and bottom of the positive electrode active material layer have a suitable conductive agent mass ratio, which is conducive to providing better conductive performance; the conductive agent mass ratio of the surface, middle and bottom of the positive electrode active material layer gradually increases with a suitable gradient, which is conducive to regulating C1 表 、C1 中 、C1 底 Gradually decreasing with a suitable gradient is beneficial to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to better infiltration of the electrolyte into the positive electrode active material layer from the outside to the inside.
[0025] In some embodiments, the porosity of the designated area on the side away from the positive electrode current collector in the two designated areas distributed along the thickness direction of the positive electrode sheet is P 外 The porosity of the designated area close to the positive electrode current collector is P 内 , P 外 <P 内 ; Optionally, (P 外 / P 内 )×100%=91.4%~96.9%.
[0026] In these embodiments, relative to the position of the positive electrode current collector, the porosity of the outer side is lower than that of the inner side. Optionally, a certain porosity ratio is maintained between the outer side and the inner side, which is beneficial to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer from the outside to the inside.
[0027] In some embodiments, at least one of the following conditions (d1) to (d3) is satisfied: (d1) the porosity of the designated area located at the first position is P 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 27.5% ≤ P 表 ≤28.3%; (d2) the porosity of the designated area located at the second position is P 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 29.2% ≤ P 中 ≤30.1%; (d3) The porosity of the designated area located at the third position is P 底 , the third position is located on the side of the positive electrode active material layer close to the positive electrode current collector; 30.6% ≤ P 底 ≤33.3%.
[0028] In these embodiments, the surface, middle and bottom of the positive electrode active material layer have appropriate porosity, which is conducive to providing better permeation performance; the porosity of the surface, middle and bottom of the positive electrode active material layer gradually increases with an appropriate gradient, which is conducive to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to better infiltration of the electrolyte into the positive electrode active material layer from the outside to the inside.
[0029] In some embodiments, the positive electrode active material in the positive electrode active material layer includes one or more of lithium iron phosphate or modified lithium iron phosphate.
[0030] In these embodiments, the positive electrode active material adopts lithium iron phosphate, which facilitates the regulation of the gradient distribution of the positive electrode active material in the positive electrode active material layer through the magnetic responsiveness of lithium iron phosphate, is beneficial to achieve the gradient design of tortuosity, mass ratio of positive electrode active material, mass ratio of binder, mass of conductive agent, etc., is beneficial to reduce the overall tortuosity of the positive electrode active material layer, and is also beneficial to improve the porosity and the uniformity of material distribution in the positive electrode active material layer.
[0031] In a second aspect, an embodiment of the present application provides a battery, comprising the positive electrode plate of the above embodiment.
[0032] In a third aspect, an embodiment of the present application provides an electrical device, comprising the battery of the above embodiment.
[0033] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;
[0036] Figure 2 An exploded view of a battery provided for some embodiments of the present application;
[0037] Figure 3 An exploded view of a battery cell provided for some embodiments of the present application;
[0038] Figure 4 A schematic cross-sectional view of a positive electrode sheet provided in some embodiments of the present application;
[0039] Figure 5 A schematic diagram of the structure of a positive electrode sheet provided in some embodiments of the present application;
[0040] Figure 6 Another schematic diagram of the structure of the positive electrode sheet provided in some embodiments of the present application;
[0041] Figure 7 A schematic diagram of a microstructure of a positive electrode sheet provided in some embodiments of the present application;
[0042] Figure 8 A schematic diagram of the structure of a battery cell provided in some embodiments and comparative examples of the present application;
[0043] Fig. 9 This is a statistical chart of liquid absorption performance when some embodiments and comparative examples of the present application are applied to battery cells.
[0044] icon:
[0045] 1000-Vehicles;
[0046] 100-battery; 200-controller; 300-motor;
[0047] 10-box; 11-first part; 12-second part; 13-accommodating space;
[0048] 20-battery cell; 21-housing; 22-electrode assembly; 23-electrode terminal; 24-pressure relief structure;
[0049] 211-housing; 212-cover; 213-sealed space;
[0050] 221-positive electrode sheet; 2211-positive electrode current collector; 2212-positive electrode active material layer; 2212a-designated area; 2212b-first position; 2212c-second position; 2212d-third position; 2212e-transmission channel; 222-isolation film; 223-negative electrode sheet;
[0051] A-thickness direction of the positive electrode sheet. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0053] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0055] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0056] In the description of the embodiments of the present application, the technical term "and / or", such as "Feature 1 and / or Feature 2", means that it can be "Feature 1" alone, it can be "Feature 2" alone, or it can be "Feature 1" plus "Feature 2". In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" relationship.
[0057] In the description of the embodiments of the present application, unless otherwise specified, the meaning of “multiple” in “one or more” is two or more than two.
[0058] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0059] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the heights, lengths, widths, and other dimensions of the various components in the embodiments of the present application shown in the drawings, as well as the overall heights, lengths, widths, and other dimensions of the integrated device are only exemplary descriptions and should not constitute any limitation to the present application.
[0060] From the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.
[0061] As the requirements for energy density increase, some technical solutions have proposed the preparation of thick electrodes, that is, increasing the thickness of the active material layer. However, the design of thick electrodes has the following problems: 1. As the thickness of the active material layer increases, it is not easy to dry the coating process, the bonding strength between the active material layer and the current collector decreases, and the active material layer is easy to fall off; at the same time, the baking temperature of the pole piece is high, and the binder and the conductive agent will float with the solvent, which can easily lead to problems such as low peeling force of the active material layer, uneven distribution of the conductive agent, and uneven distribution of pores. 2. As the thickness of the active material layer increases, it becomes more difficult for the electrolyte to penetrate the active material layer, and it is easy to affect the rate performance of the battery due to the incomplete infiltration of the active material layer by the electrolyte; 3. The increase in the active material layer will extend the transmission path of electrons and lithium ions, reduce the ion and electron conductivity, and lead to poor rate performance and cycle performance.
[0062] Among them, the electrolyte wettability of the positive electrode plate is a factor that affects the battery performance. In order to improve the technical solution of the wettability in view of the above problems, some current studies have improved the overall wettability of the active material layer by changing the morphology of the transmission channel in the active material layer. For example, in some technical solutions, the magnetic material is oriented in the high-nickel positive electrode slurry by alternately loading and removing the magnetic field, and at the same time, the ice crystal effect is constructed to prepare a thick plate with hierarchical multi-dimensional through-channels. However, the method of constructing the transmission channel usually has a complex process and high process requirements.
[0063] Based on this, the present application provides a positive electrode plate, considering that in the process of electrolyte infiltration of the positive electrode active material layer, the electrolyte infiltrates from the outside to the inside, and the infiltration speed is usually slower and more difficult as it goes inward. In the embodiment of the present application, the positive electrode active material layer is gradient designed, and the gradient control method is relatively easy to implement; wherein, by regulating the tortuosity of the outside to be greater than the tortuosity of the inside, the permeation performance of the inside is made better than the permeation capacity of the outside, thereby increasing the speed of electrolyte infiltration inside, which is conducive to the electrolyte infiltration of the positive electrode active material layer from the outside to the inside, and can increase the liquid absorption rate and liquid absorption amount of the positive electrode active material layer, thereby improving the electrolyte infiltration performance of the positive electrode active material layer, which is conducive to improving the rate performance.
[0064] The battery cell using the positive electrode sheet disclosed in the embodiment of the present application can be used in, but not limited to, electrical devices such as vehicles, ships or aircraft. The embodiment of the present application provides an electrical device using a battery as a power source, and the electrical device can be, but not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, the electric toy can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and the spacecraft can include airplanes, rockets, space shuttles, and spacecrafts, and the like.
[0065] For the convenience of explanation, the following embodiments are described by taking a vehicle as an example of an electrical device in an embodiment of the present application.
[0066] See also Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.
[0067] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0068] In the present application, the battery 100 refers to a single physical module including one or more battery cells 20 to provide a certain voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The battery 100 may include a box 10 for encapsulating one or more battery cells 20, and the box 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0069] See also Figure 2 , Figure 2An exploded view of a battery 100 provided for some embodiments of the present application. The battery 100 includes a box 10 and a plurality of battery cells 20, and the plurality of battery cells 20 are accommodated in the box 10. Among them, the box 10 is used to accommodate the battery cells 20, and the box 10 can be a variety of structures. In some embodiments, the box 10 can include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a receiving space 13 for accommodating the battery cells 20. The second part 12 can be a hollow structure with one end open, the first part 11 is a plate-like structure, and the first part 11 covers the open side of the second part 12 to form a box 10 with a receiving space 13; the first part 11 and the second part 12 can also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12 to form a box 10 with a receiving space 13. Of course, the first part 11 and the second part 12 can be a variety of shapes, such as a cylinder, a cuboid, etc.
[0070] In the battery 100, multiple battery cells 20 can be connected in series, in parallel, or in a hybrid connection. A hybrid connection means that multiple battery cells 20 are both connected in series and in parallel. Multiple battery cells 20 can be directly connected in series, in parallel, or in a hybrid connection, and then the whole formed by multiple battery cells 20 is accommodated in the box 10. Alternatively, multiple battery cells 20 can be connected in series, in parallel, or in a hybrid connection to form a module, and multiple modules can be connected in series, in parallel, or in a hybrid connection to form a whole, and then accommodated in the box 10. The battery 100 can also include other structures. For example, multiple battery cells 20 can be electrically connected through a busbar component to achieve parallel, series, or hybrid connection of multiple battery cells 20.
[0071] The battery cell 20 refers to the smallest unit constituting the battery pack and can be a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery or a magnesium-ion battery, but is not limited thereto.
[0072] See also Figure 3 The battery cell 20 may include a housing 21 , an electrode assembly 22 and an electrolyte, and both the electrode assembly 22 and the electrolyte are contained in the housing 21 .
[0073] The housing 21 may include a shell 211 and a cover 212. The shell 211 is a component used to cooperate with the cover 212 to form an internal sealed space 213 of the battery cell 20, wherein the formed sealed space 213 can be used to accommodate the electrode assembly 22, electrolyte and other components. The cover 212 refers to a component that covers the opening of the shell 211 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the cover 212 can be adapted to the shape of the shell 211 to cooperate with the shell 211, and the cover 212 may also be provided with functional components such as electrode terminals 23 and pressure relief structures 24. A sealing ring may be configured between the opening of the shell 211 and the cover 212 to achieve sealing between the shell 211 and the cover 212.
[0074] The shell 211 and the cover 212 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shapes of the shell 211 and the cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The shell 211 and the cover 212 can be made of various materials, such as but not limited to metals such as copper, iron, aluminum, stainless steel, and aluminum alloy. The sealing ring can be made of various materials, such as but not limited to PP (polypropylene), PC (polycarbonate), PET (polyethylene terephthalate) and other materials that are resistant to electrolyte corrosion, high toughness and fatigue resistance. A coating can be formed on the outer surface of the shell 211, and the material of the coating can be various, such as but not limited to corrosion-resistant materials such as Ni and Cr.
[0075] The battery cell 20 may also be in a soft pack form, such as a bag-type soft pack. The material of the soft pack may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0076] The electrode assembly 22 includes a negative electrode sheet, a separator and a positive electrode sheet 221 (see Figure 4 and Figure 5 ). The battery cell 20 mainly relies on the movement of metal ions between the positive electrode sheet 221 and the negative electrode sheet to work. During the charge and discharge process, the active ions are embedded and removed back and forth between the positive electrode sheet 221 and the negative electrode sheet; the isolation film is arranged between the positive electrode sheet 221 and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The electrode assembly 22 can be a winding structure or a stacked structure, and the embodiments of the present application are not limited to this.
[0077] The negative electrode sheet includes a negative electrode collector, a negative electrode tab and a negative electrode active material layer. The negative electrode active material layer is arranged on at least one side of the negative electrode collector. A primer layer may also be arranged between the negative electrode active material layer and the negative electrode collector. The negative electrode tab protrudes from the negative electrode collector. The negative electrode tab is located at one end or two opposite ends of the negative electrode collector, for example.
[0078] Among them, the negative electrode current collector can be a metal foil or a composite current collector. For example, the material of the negative electrode current collector and the negative electrode tab can be copper. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0079] The negative electrode active material in the negative electrode active material layer may be a negative electrode active material such as carbon and silicon. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active material materials may also be used.
[0080] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0081] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0082] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0083] The isolation membrane is located between the positive electrode plate 221 and the negative electrode plate, and plays an isolation role. The embodiment of the present application has no particular restriction on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0084] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0085] See also Figure 4 The positive electrode sheet 221 includes a positive electrode collector 2211 and a positive electrode active material layer 2212. The positive electrode active material layer 2212 is arranged on at least one side of the positive electrode collector 2211, that is, the positive electrode active material layer 2212 can be arranged on one side or both sides of the positive electrode collector 2211; a primer layer can also be arranged between the positive electrode active material layer 2212 and the positive electrode collector 2211.
[0086] Among them, the positive electrode current collector 2211 can be a metal foil or a composite current collector, for example, the material of the positive electrode current collector 2211 can be aluminum. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material base layer, and the composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0087] The design requirements of the positive electrode active material layer 2212 can be designed according to the technical solutions proposed in the embodiments of the present application, unless otherwise specified.
[0088] In some embodiments, the positive electrode active material layer 2212 may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0089] In some embodiments, the positive active material layer 2213 may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0090] Next, the positive electrode plate 221 proposed in the embodiment of the present application is described in detail.
[0091] See also Figure 4 and Figure 5In a first aspect, an embodiment of the present application provides a positive electrode sheet 221, the positive electrode sheet 221 includes a positive current collector 2211 and a positive active material layer 2212, the positive current collector 2211 and the positive active material layer 2212 are distributed along the thickness direction A of the positive electrode sheet; wherein, a plurality of designated areas 2212a at different positions are taken in the positive active material layer 2212, along the thickness direction A of the positive electrode sheet, 50 μm ≤ the thickness of the designated area 2212a < the thickness of the positive active material layer 2212, satisfying: in the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the tortuosity of the designated area 2212a on the side away from the positive current collector 2211 is T 外 The tortuosity of the designated area 2212a on the side of the positive electrode current collector 2211 is T 内 , T 外 >T 内 .
[0092] Taking multiple designated areas 2212a at different positions in the positive electrode active material layer 2212 means that different designated areas 2212a are taken from different positions, and each designated area 2212a corresponds to a designated position. The designated area 2212a refers to a local area in the positive electrode active material layer 2212 that meets the specified thickness requirement; as an example, in a cross section perpendicular to the thickness direction A of the positive electrode pole piece, the size of the designated area is consistent with the size of the positive electrode active material layer 2212. The designated area 2212a is used as a definition for dividing the positive electrode active material layer 2212 into regions, and its position in the positive electrode active material layer 2212 is not limited, as long as it meets the specified thickness requirement; with respect to two designated areas 2212a, the thickness of the two can be the same or different, and the two are illustratively the same. As an example, along the thickness direction A of the positive electrode pole piece, the thickness of the designated area 2212a is 50μm to 60μm, for example, 50μm.
[0093] See also Figure 5 In some examples, in the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the two designated areas 2212a are sequentially arranged along the thickness direction A of the positive electrode sheet, and the boundaries between the two overlap. As an example, the two opposite surfaces of the designated areas 2212a distributed along the thickness direction A of the positive electrode sheet are perpendicular to the thickness direction A of the positive electrode sheet.
[0094] In the embodiment of the present application, in the description of the designated area 2212a on the side away from the positive current collector 2211, that is, the outer designated area 2212a and the designated area 2212a on the side close to the positive current collector 2211, that is, the inner designated area 2212a, both the outer side and the inner side are relative to the position of the positive current collector 2211, and will not be repeated later. In the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the outer designated area 2212a refers to the designated area 2212a relatively far away from the positive current collector 2211, and the inner designated area 2212a refers to the designated area 2212a relatively close to the positive current collector 2211.
[0095] Tortuosity is common knowledge in the art and has a well-known meaning in the art, and can be measured by instruments and testing methods known in the art; taking the tortuosity of the positive electrode active material layer 2212 as an example, it refers to the ratio of the distance length and displacement of the transmission channel 2212e in the positive electrode active material layer 2212 from one side surface to the other side surface of the positive electrode active material layer 2212. The tortuosity reflects the transmission channel 2212e in the positive electrode active material layer 2212 (see Figure 7 ) is tortuosity. The smaller the tortuosity, the smaller the tortuosity of the transmission channel 2212e, and the better the corresponding permeation performance. As an example, the tortuosity test method includes: 1) the thickness of the electrode (d, cm), the surface area (A, cm 2 ) measurement; 2) measurement of the electrode porosity (ε, %); 3) measurement of the electrolyte ion conductivity (k, S / cm); 4) measurement of electrochemical impedance spectroscopy (EIS), based on the extrapolation of the low-frequency region to obtain the high-frequency resistance and the ionic impedance in the pores (R ion , Ω); 5) Calculate the tortuosity (τ) according to the above test results, τ=ε*k*R ion *A / d.
[0096] It should be noted that in the present application, when testing the parameters related to the positive electrode active material layer 2212, the entire positive electrode active material layer 2212 of the positive electrode sheet 2212 can be peeled off for testing, or the positive electrode sheet 2212 can be cut into small samples, and the area of the single side surface of the small sample is close to 1000mm 2 , peel off the entire positive electrode active material layer 2212 on the sample for testing. When testing the relevant parameters of the designated area 2212a, a local area that meets the thickness requirement can be cut out of the entire positive electrode active material layer 2212 of the positive electrode sheet 2212 for testing; or the positive electrode sheet 2212 can be cut into a sample, and then a local area that meets the thickness requirement can be cut out of the positive electrode active material layer 2212 of the sample for testing.
[0097] In the technical solution of the embodiment of the present application, relative to the position of the positive electrode current collector 2211, the tortuosity of the outer designated area 2212a is greater than the tortuosity of the inner designated area 2212a, so that the inner designated area 2212a has better seepage performance, which is beneficial for the electrolyte to infiltrate the positive electrode active material layer 2212 from the outside to the inside, and can increase the liquid absorption rate and liquid absorption amount of the positive electrode active material layer 2212, thereby improving the electrolyte infiltration performance of the positive electrode active material layer 2212, which is beneficial to improving the rate performance.
[0098] In some embodiments, T 外 / T 内 =1.07~1.24; Optionally, T 外 / T 内 =1.09~1.17; Optionally, T 外 / T 内 =1.09~1.16.
[0099] As an example, T 外 / T 内 The value of may be, for example but not limited to, any one of 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24 or a range between any two of them.
[0100] In these embodiments, relative to the position of the positive electrode current collector 2211, a certain tortuosity ratio is maintained between the outside and the inside, and the permeability performance of the designated area 2212a on the inside is improved to a certain extent relative to the outside, which is conducive to better infiltration of the electrolyte into the positive electrode active material layer 2212 from the outside to the inside.
[0101] See also Figure 6 In some embodiments, at least one of the following conditions (a1) to (a3) is satisfied: (a1) The tortuosity of the designated area 2212a at the first position 2212b is T 表 , the first position 2212b is located on the side of the positive electrode active material layer 2212 away from the positive electrode current collector 2211, 1.60≤T 表 ≤2.05; optionally, 1.70≤T 表 ≤1.75; (a2) the tortuosity of the designated area 2212a at the second position 2212c is T 中 , the second position 2212c passes through the midpoint of the thickness of the positive electrode active material layer 2212, 1.50≤T 中 ≤1.65; optionally, 1.50≤T 中≤1.55; (a3) The tortuosity of the designated area 2212a at the third position 2212d is T 底 , the third position 2212d is located on the side of the positive electrode active material layer 2212 close to the positive electrode current collector 2211; 1.30≤T 底 ≤1.55; optionally, 1.30≤T 底 ≤1.35.
[0102] In the embodiment of the present application, as an example, the designated area 2212a at the first position 2212b, its side away from the positive current collector 2211 is located on the surface of the positive active material layer 2212, that is, the side of the positive active material layer 2212 away from the positive current collector 2211 is the side boundary of the designated area 2212a at the first position 2212b; the designated area 2212a at the second position 2212c, its thickness midpoint is consistent with the thickness midpoint of the positive active material layer 2212; the designated area 2212a at the second position 2212c, its side close to the positive current collector 2211 is located on the bottom surface of the positive active material layer 2212, that is, the side of the positive active material layer 2212 close to the positive current collector 2211 is the side boundary of the designated area 2212a at the third position 2212d. In the following text, the relevant description can refer to the description here, and will not be repeated later. As an example, the designated area 2212a at the first position 2212b recorded in different embodiments refers to the same designated area 2212a, and the designated area 2212a at the second position 2212c and the designated area 2212a at the second position 2212c are explained with reference to the above description.
[0103] In the embodiments of the present application, the midpoint of the thickness of the specified structure refers to the midpoint of the specified structure in the thickness direction A of the positive electrode sheet.
[0104] As an example, T 表 The value of may be, for example but not limited to, any one of 1.60, 1.65, 1.70, 1.71, 1.72, 1.73, 1.74, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05 or a range between any two of them.
[0105] As an example, T 中 The value of is, for example but not limited to, any one of 1.50, 1.51, 1.52, 1.53, 1.54, 1.55, 1.60, 1.65 or a range between any two of them.
[0106] As an example, T 底The value of may be, for example but not limited to, any one of 1.30, 1.31, 1.32, 1.33, 1.34, 1.35, 1.40, 1.45, 1.50, 1.55 or a range between any two of them.
[0107] In these embodiments, the surface, middle and bottom of the positive electrode active material layer 2212 have a smaller tortuosity, which is conducive to faster infiltration of the electrolyte into the surface, middle and bottom of the positive electrode active material layer 2212; the tortuosity of the surface, middle and bottom of the positive electrode active material layer 2212 gradually decreases with a suitable gradient, which is conducive to better infiltration of the electrolyte into the positive electrode active material layer 2212 from the outside to the inside.
[0108] In some embodiments, the tortuosity of the positive electrode active material layer 2212 is T 总 , 1.45≤T 总 ≤1.75; optionally, 1.50≤T 总 ≤1.70.
[0109] As an example, T 总 The value of may be, for example but not limited to, any one of 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75 or a range between any two of them.
[0110] In an embodiment of the present application, the designated area 2212a at the first position 2212b, the designated area 2212a at the second position 2212c, and the designated area 2212a at the third position 2212d are sampled, for example, in the following manner: starting from the surface of the positive electrode active material layer 2212, a local area that meets the thickness requirement is cut to obtain the designated area 2212a at the first position 2212b; scraping off excess positive electrode active material until it approaches the midpoint of the thickness of the positive electrode active material layer 2212, and then taking this as the starting position, cutting off a local area that meets the thickness requirement to obtain the designated area 2212a at the second position 2212c; and continuing to scrape off excess positive electrode active material until it approaches the positive current collector 2211, the remaining positive electrode active material is peeled off from the positive current collector 2211, and the designated area 2212a at the third position 2212d is obtained.
[0111] In these embodiments, the positive electrode active material layer 2212 includes positive electrode active material; the positive electrode active material layer 2212 has a smaller tortuosity as a whole, and the tortuosity close to 1 indicates that the transmission channel 2212e in the positive electrode active material layer 2212 extends in a thickness direction A close to the positive electrode sheet, which is conducive to faster infiltration of the electrolyte in the positive electrode active material layer 2212 as a whole.
[0112] In some embodiments, in the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the mass proportion of the positive electrode active material in the designated area 2212a on the side away from the positive electrode current collector 2211 is C1 外 The mass ratio of the positive electrode active material in the designated area 2212a close to the positive electrode current collector 2211 is C1 内 , C1 外 -C1 内 =0.1%~1.2%; Optionally, C1 外 -C1 内 =0.1%~1.0%.
[0113] The mass proportion of the positive electrode active material can be measured by instruments and test methods known in the art. As an example, the sample to be tested is digested, and then the element composition and mass fraction of the digestion solution are measured by ICP (inductively coupled plasma emission spectrometry), and the mass proportion of the positive electrode active material in the corresponding designated area 2212a is calculated based on the test results.
[0114] As an example, C1 外 Subtract C1 内 The result value may be, for example but not limited to, any point value among 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2% or a range between any two of them.
[0115] In these embodiments, C1 外 Higher than C1 内 A certain range is conducive to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0116] See also Figure 6 In some embodiments, at least one of the following conditions (b1) to (b3) is satisfied: (b1) The mass ratio of the positive electrode active material in the designated area 2212a located at the first position 2212b is C1 表 , the first position 2212b is located on the side of the positive electrode active material layer 2212 away from the positive electrode current collector 2211, 97.4%≤C1 表 ≤98.1%; optionally, 97.4%≤C1 表 ≤98.0%; (b2) The mass ratio of the positive electrode active material in the designated area 2212a located at the second position 2212c is C1 中 The second position 2212c passes through the midpoint of the thickness of the positive electrode active material layer 2212, 96.7% ≤ C1 中≤97.3%; optionally, 97.1%≤C1 中 ≤97.2%; (b3) The mass ratio of the positive electrode active material in the designated area 2212a located at the third position 2212d is C1 底 , the third position 2212d is located on the side of the positive electrode active material layer 2212 close to the positive electrode current collector 2211; 95.9%≤C1 底 ≤96.9%; optionally, 96.4%≤C1 底 ≤96.6%.
[0117] As an example, C1 表 The value may be, for example but not limited to, any one of 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98.0%, 98.1% or a range between any two of them.
[0118] As an example, C1 中 The value may be, for example but not limited to, any one of 96.7%, 96.8%, 96.9%, 97.0%, 97.1%, 97.2%, 97.3% or a range between any two of them.
[0119] As an example, C1 底 The value may be, for example but not limited to, any point value among 95.9%, 96.0%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 96.6%, 96.7%, 96.8%, 96.9% or a range between any two of them.
[0120] In these embodiments, the surface, middle and bottom of the positive electrode active material layer 2212 have a larger positive electrode active material mass ratio, which is conducive to providing a higher energy density; the positive electrode active material mass ratio of the surface, middle and bottom of the positive electrode active material layer 2212 gradually decreases with a suitable gradient, which is conducive to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0121] In some embodiments, the positive electrode active material layer 2212 includes a binder; in the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the binder mass proportion in the designated area 2212a on the side away from the positive electrode current collector 2211 is C2 外 The mass ratio of the binder in the designated area 2212a close to the positive electrode current collector 2211 is C2 内 , C2 内 -C2 外=0.05%~0.8%; Optionally, C2 内 -C2 外 =0.05%~0.45%.
[0122] The mass percentage of the binder can be measured by instruments and test methods known in the art. As an example, the test method for the mass percentage of the binder includes: differential scanning thermogravimetric analysis, placing the pole piece in synchronous thermal analysis, recording the change in sample weight during the temperature increase process, and calculating the mass percentage of the binder according to the thermogravimetric curve. As an example, the binder includes or is polyvinylidene fluoride (PVDF), and the thermogravimetric heating temperature is, for example, 350°C to 390°C.
[0123] As an example, C2 内 Subtract C2 外 The result value may be, for example but not limited to, any point value among 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8% or a range between any two of them.
[0124] In these embodiments, C2 外 Lower than C2 内 A certain range is conducive to regulating C1 外 Higher than C1 内 A certain range, which is conducive to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0125] See also Figure 6 In some embodiments, at least one of the following conditions (c1) to (c3) is satisfied: (c1) The mass proportion of the adhesive in the designated area 2212a located at the first position 2212b is C2 表 , the first position 2212b is located on the side of the positive electrode active material layer 2212 away from the positive electrode current collector 2211, 0.5%≤C2 表 ≤1.0%; optionally, 0.6%≤C2 表 ≤0.9%; (c2) The mass proportion of the adhesive in the designated area 2212a located at the second position 2212c is C2 中 , the second position 2212c passes through the midpoint of the thickness of the positive electrode active material layer 2212, 1.0%≤C2 中 ≤1.3%; optionally, 1.0%≤C2 中 ≤1.1%;
[0126] (c3) The mass ratio of the adhesive in the designated area 2212a located at the third position 2212d is C2 底, the third position 2212d is located on the side of the positive electrode active material layer 2212 close to the positive electrode current collector 2211; 1.3%≤C2 底 ≤1.8%; optionally, 1.5%≤C2 底 ≤1.8%; optionally, 1.5%≤C2 底 ≤1.7%.
[0127] As an example, C2 表 The value may be, for example but not limited to, any one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or a range between any two of them.
[0128] As an example, C2 中 The value may be, for example but not limited to, any one of 1.0%, 1.1%, 1.2%, 1.3% or a range between any two of them.
[0129] As an example, C2 底 The value may be, for example but not limited to, any one of 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8% or a range between any two of them.
[0130] In these embodiments, the surface, middle and bottom of the positive electrode active material layer 2212 have a suitable binder mass ratio, which is conducive to providing better bonding performance; the binder mass ratio of the surface, middle and bottom of the positive electrode active material layer 2212 gradually increases with a suitable gradient, which is conducive to regulating C1 表 、C1 中 、C1 底 Gradually decreasing with a suitable gradient is beneficial to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to better infiltration of the electrolyte into the positive electrode active material layer 2212 from the outside to the inside, and is also conducive to improving the overall structural stability of the positive electrode active material layer 2212.
[0131] In some embodiments, the positive electrode active material layer 2212 includes a conductive agent; in the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the conductive agent mass ratio in the designated area 2212a on the side away from the positive electrode current collector 2211 is C3 外 The mass proportion of the conductive agent in the designated area 2212a close to the positive electrode current collector 2211 is C3 内 , C3 内 -C3 外 =0.2%~0.8%; Optionally, C3 内 -C3 外 =0.2%~0.45%.
[0132] The mass percentage of the conductive agent can be measured by instruments and test methods known in the art. As an example, the test method for the mass percentage of the conductive agent includes: The test method for the mass percentage includes: differential scanning thermogravimetric analysis, placing the pole piece in synchronous thermal analysis, recording the change in sample weight during the temperature increase process, and calculating the mass percentage of the conductive agent according to the thermogravimetric curve. As an example, the conductive agent includes or is a carbon black conductive agent, and the thermal gravimetric heating temperature is, for example, 450°C to 500°C.
[0133] As an example, C3 内 Subtract C3 外 The result value may be, for example but not limited to, any point value among 0.2%, 0.3%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8% or a range between any two of them.
[0134] In these embodiments, C3 外 Lower than C3 内 A certain range is conducive to regulating C1 外 Higher than C1 内 A certain range, which is conducive to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0135] See also Figure 6 In some embodiments, at least one of the following conditions (c1) to (c3) is satisfied: (c1) The mass proportion of the conductive agent in the designated area 2212a located at the first position 2212b is C3 表 , the first position 2212b is located on the side of the positive electrode active material layer 2212 away from the positive electrode current collector 2211, 0.7%≤C3 表 ≤1.4%; optionally, 0.9%≤C3 表 ≤1.4%; optionally, 0.9%≤C3 表 ≤1.2%; (c2) The mass proportion of the conductive agent in the designated area 2212a located at the second position 2212c is C3 中 , the second position 2212c passes through the midpoint of the thickness of the positive electrode active material layer 2212, 1.1%≤C3 中 ≤1.7%; optionally, 1.2%≤C3 中 ≤1.7%; optionally, 1.2%≤C3 中 ≤1.3%;
[0136] (c3) The mass ratio of the conductive agent in the designated area 2212a located at the third position 2212d is C3 底, the third position 2212d is located on the side of the positive electrode active material layer 2212 close to the positive electrode current collector 2211; 1.2%≤C3 底 ≤2.0%; optionally, 1.5%≤C3 底 ≤2.0%; optionally, 1.5%≤C3 底 ≤1.7%.
[0137] As an example, C3 表 The value may be, for example but not limited to, any point value among 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, or a range between any two of them.
[0138] As an example, C3 中 The value may be, for example but not limited to, any one of 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7% or a range between any two of them.
[0139] As an example, C3 底 The value may be, for example but not limited to, any point value among 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or a range between any two of them.
[0140] In these embodiments, the surface, middle and bottom of the positive electrode active material layer 2212 have a suitable conductive agent mass ratio, which is conducive to providing better conductive performance; the conductive agent mass ratio of the surface, middle and bottom of the positive electrode active material layer 2212 gradually increases with a suitable gradient, which is conducive to regulating C1 表 、C1 中 、C1 底 Gradually increasing with a suitable gradient is beneficial to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0141] In some embodiments, in the two designated areas 2212a distributed along the thickness direction A of the positive electrode sheet, the porosity of the designated area 2212a on the side away from the positive electrode current collector 2211 is P 外 The porosity of the designated area 2212a close to the positive electrode current collector 2211 is P 内 , P 外 <P 内 ; Optionally, (P 外 / P 内 )×100%=91.4%~96.9%.
[0142] Porosity is common knowledge in the art, has a well-known meaning in the art, and can be measured by instruments and testing methods known in the art. As an example, the porosity testing method includes: calculating the apparent volume; placing a sample cup containing a sample in a true density tester, a closed testing system, introducing helium according to a program, detecting the pressure of the gas in the sample chamber and the expansion chamber, and then calculating the real volume according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested based on the real volume and the apparent volume.
[0143] As an example, (P 外 / P 内 )×100% may take values such as but not limited to 91.4%, 91.9%, 92.4%, 92.9%, 93.4%, 93.9%, 94.4%, 94.9%, 95.4%, 95.9%, 96.4%, 96.9%, any one of the points or a range between any two of them.
[0144] In these embodiments, relative to the position of the positive electrode current collector 2211, the porosity of the outer side is lower than the porosity of the inner side. Optionally, a certain porosity ratio is maintained between the outer side and the inner side, which is beneficial to regulating T 外 , T 内 The two satisfy a suitable gradient, which is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0145] In some embodiments, at least one of the following conditions (d1) to (d3) is satisfied: (d1) The porosity of the designated area 2212a located at the first position 2212b is P 表 , the first position 2212b is located on the side of the positive electrode active material layer 2212 away from the positive electrode current collector 2211, 27.5%≤P 表 ≤28.3%; (d2) The porosity of the designated area 2212a located at the second position 2212c is P 中 , the second position 2212c passes through the midpoint of the thickness of the positive electrode active material layer 2212, 29.2%≤P 中 ≤30.1%; (d3) The porosity of the designated area 2212a located at the third position 2212d is P 底 , the third position 2212d is located on the side of the positive electrode active material layer 2212 close to the positive electrode current collector 2211; 30.6%≤P 底 ≤33.3%.
[0146] As an example, P 表 The value may be, for example but not limited to, any point value among 27.5%, 27.6%, 27.7%, 27.8%, 27.9%, 28.0%, 28.1%, 28.2%, 28.3% or a range value between any two of them.
[0147] As an example, P 中 The value may be, for example but not limited to, any point value among 29.2%, 29.3%, 29.4%, 29.5%, 29.6%, 29.7%, 29.8%, 29.9%, 30.0%, 30.1% or a range between any two of them.
[0148] As an example, P 底 The value may be, for example but not limited to, any point value among 30.6%, 31.0%, 31.5%, 32.0%, 32.5%, 33.0%, 33.3% or a range value between any two of them.
[0149] In these embodiments, the surface, middle and bottom of the positive electrode active material layer 2212 have appropriate porosity, which is conducive to providing better permeation performance; the porosity of the surface, middle and bottom of the positive electrode active material layer 2212 gradually increases with an appropriate gradient, which is conducive to regulating T 表 , T 中 , T 底 Gradually decreasing with a suitable gradient is conducive to the electrolyte better infiltrating the positive electrode active material layer 2212 from the outside to the inside.
[0150] In some embodiments, the positive active material in the positive active material layer 2212 includes one or more of lithium iron phosphate or modified lithium iron phosphate, lithium iron phosphate containing doped elements, or lithium iron phosphate containing a coating layer.
[0151] The modified lithium iron phosphate may be modified by doping, by coating, or by both doping and coating.
[0152] In the electrode made by the traditional granular slurry coating method, the pore distribution is uneven and the tortuosity is high. In these embodiments, the positive active material is lithium iron phosphate, which is convenient for regulating the gradient distribution of the positive active material in the positive active material layer 2212 through the magnetic responsiveness of lithium iron phosphate, which is conducive to achieving the gradient design of tortuosity, mass proportion of positive active material, mass proportion of binder, mass of conductive agent, etc., which is conducive to reducing the overall tortuosity of the positive active material layer 2212, and is also conducive to improving the porosity and the uniformity of material distribution in the positive active material layer 2212.
[0153] See also Figure 7In some exemplary embodiments, along the thickness direction A of the positive electrode sheet, from the side of the positive active material layer 2212 away from the positive current collector 2211 to the side close to the positive current collector 2211, the tortuosity and the mass proportion of the positive active material are decreasing, while the mass proportion of the binder, the mass proportion of the conductive agent, and the porosity are increasing. In the positive active material layer 2212, the extension direction of the transmission channel 2212e extends close to the thickness direction A of the positive electrode sheet, that is, the extension direction of the transmission channel 2212e is close to the surface of the positive current collector 2211. The relationship is perpendicular.
[0154] In the above exemplary embodiments, the decreasing trend and the increasing trend may be a continuous change trend, ie, a gradual change; or a step-wise change trend, ie, maintaining a certain value in a certain area and then changing to another value in the next area.
[0155] The embodiment of the present application provides a method for preparing the above-mentioned positive electrode plate, including: using magnetic particles of positive electrode active material to prepare a slurry for coating, and then applying an external magnetic field to make the magnetic particles move in a directional manner to achieve the gradient design of the positive electrode active material layer in the above-mentioned embodiment.
[0156] Optionally, when applying the external magnetic field, the external magnetic field is perpendicular to the surface of the slurry layer.
[0157] Optionally, after an external magnetic field is applied to direct the movement of the magnetic particles, a phase inversion method is used to form a gradient-changing transmission channel in the positive electrode active material layer.
[0158] Exemplarily, the second method for preparing the positive electrode sheet includes:
[0159] S1: Preparation of magnetic nano-lithium iron phosphate.
[0160] The magnetic nanoparticles are coated with a cationic dispersant to make them positively charged; the operation includes: dissolving 1 part by weight of the magnetic nanoparticles in 5 parts by weight of the cationic dispersant, stirring in a 60°C oil bath for 2 hours, and drying at 60°C to obtain the magnetic nanoparticles coated with the cationic dispersant. The magnetic nanoparticles include but are not limited to magnetic nano Fe3O4 and gadolinium gallium garnet magnetic nanoparticles. Then, 1 part by weight of lithium iron phosphate is dispersed in 40 parts by weight of distilled water by magnetic stirring, and 0.0075 parts by weight of the magnetic nanoparticles coated with the cationic dispersant are diluted in 15 parts by weight of distilled water, and then added to the stirred dispersion, mixed and stirred for 2 hours, the suspension is centrifuged and the magnetic nano lithium iron phosphate particles are collected, and dried in a vacuum oven at 90°C overnight.
[0161] Among them, the cationic dispersant can optionally include ammonium salt type and / or quaternary ammonium salt type dispersants, for example, dialkyl dimethyl ammonium chloride, such as but not limited to (4-vinylpyridine)-acrylamide-DMC copolymer (abbreviated as PVAD), styrene-acrylamide-DMC copolymer (abbreviated as PSAD), styrene-(4-vinylpyridine)-DMC copolymer (abbreviated as PSVD), etc.
[0162] S2: Slurry preparation.
[0163] The magnetic nano lithium iron phosphate, the conductive agent and the binder are weighed, dispersed in N-methylpyrrolidone (NMP) solvent, and stirred evenly to form a slurry with good uniformity.
[0164] S3: coating.
[0165] The slurry is coated on the aluminum foil substrate by coating methods such as extrusion coating, transfer coating, spraying, and intermittent coating to ensure the uniformity of the coating material.
[0166] S4: External magnetic field.
[0167] After coating, an external magnetic field perpendicular to the pole piece is turned on to make the magnetic nano-lithium iron phosphate move in a directional manner to form a gradient distribution of the positive electrode active material. Optionally, the magnetic field is 5T to 10T and lasts for 2min to 5min.
[0168] S5: Water bath.
[0169] Place the positive electrode sheet in a water bath for, for example, 1 hour, and use the phase inversion method to cause a solution phase transition. The organic solvent in the positive electrode sheet will transfer to the flocculant pool, causing the positive electrode sheet to solidify and form a trapezoidal vertical channel.
[0170] The flocculant is, for example but not limited to, water, ethanol, a water / ethanol mixture, and the like.
[0171] Step S6: Drying.
[0172] The dried electrode is obtained by vacuum drying, displacement drying, dielectric drying, etc. Optionally, the environmental conditions of vacuum drying include: vacuum degree of about 1 kPa, temperature of 80° C. to 120° C., and water content of less than 600 ppm.
[0173] Step S7: Polishing.
[0174] The surface layer produced during the phase inversion process is removed by polishing, such as Ar ion polishing.
[0175] In different embodiments, T can be adjusted by adjusting 1) the coating state of the cationic dispersant on the magnetic nanoparticles; 2) the uniformity of the slurry; 3) the perpendicularity between the magnetic field and the pole piece, the uniformity of the magnetic field, the magnitude of the magnetic field force; 4) the temperature and time of the water bath, etc. 外 , T 内 、C1 外 、C1 内 、C2 外 、C2 内 、C3 外 、C3 内 Parameters corresponding to the microstructure.
[0176] In a second aspect, an embodiment of the present application provides a battery 100, comprising the positive electrode plate 221 of the above embodiment.
[0177] In a third aspect, an embodiment of the present application provides an electrical device, comprising the battery 100 of the above embodiment.
[0178] Some specific embodiments are listed below to better illustrate the present application.
[0179] 1. Preparation of battery cells
[0180]
Preparation of positive electrode
[0181] The preparation method corresponding to the embodiment is as follows:
[0182] S1: Preparation of magnetic nano-lithium iron phosphate.
[0183] The magnetic nanoparticles are coated with a cationic dispersant to make them positively charged; the operation includes: dissolving 1 part by weight of the magnetic nanoparticles in 5 parts by weight of the cationic dispersant, stirring in a 60°C oil bath for 2 hours, and drying at 60°C to obtain the magnetic nanoparticles coated with the cationic dispersant. The cationic dispersant is PVAD, and the magnetic nanoparticles are magnetic nano-Fe3O4. Then, 1 part by weight of lithium iron phosphate is dispersed in 40 parts by weight of distilled water by magnetic stirring, and 0.0075 parts by weight of the magnetic nanoparticles coated with the cationic dispersant are diluted in 15 parts by weight of distilled water, and then added to the stirred dispersion, mixed and stirred for 2 hours, the suspension is centrifuged and the magnetic nano lithium iron phosphate particles are collected, and dried in a vacuum oven at 90°C overnight.
[0184] S2: Slurry preparation.
[0185] Magnetic nano lithium iron phosphate, conductive carbon, and binder polyvinylidene fluoride (PVDF) are weighed according to a certain mass ratio, and a certain amount of surfactant additive polyethoxy methacrylate (PMA) is added, dispersed in N-methylpyrrolidone (NMP) solvent, and evenly stirred to form a slurry with good uniformity.
[0186] S3: coating.
[0187] The slurry was coated on both sides at 0.314 mg / mm 2 The coating weight is coated on a 13μm aluminum foil substrate to ensure the uniformity of the coating material.
[0188] S4: External magnetic field.
[0189] After coating, the external magnetic field perpendicular to the pole piece is turned on to make the magnetic nano-lithium iron phosphate move in a directional manner, forming a gradient distribution of the positive electrode active material, and the adhesive and the conductive agent are distributed in a gradient accordingly. At this time, refer to Figure 7 From the side of the positive electrode active material layer far away from the positive electrode current collector to the side close to the positive electrode current collector, the mass proportion of the positive electrode active material tends to decrease, and the mass proportion of the binder, the mass proportion of the conductive agent, and the porosity tend to increase, so that the tortuosity ratio tends to decrease.
[0190] In Examples 1 to 5, the conditions of step S4 are slightly different. In Example 1, the magnetic field is 8T and the duration is 200s; in Example 2, the magnetic field is 8T and the duration is 175s; in Example 3, the magnetic field is 8T and the duration is 150s; in Example 4, the magnetic field is 9T and the duration is 200s; in Example 5, the magnetic field is 7T and the duration is 200s.
[0191] S5: Water bath.
[0192] The positive electrode plate is placed in a 45°C water bath for 1 hour, and the phase inversion method is used to cause the solution phase to change. The organic solvent in the positive electrode plate will be transferred to the flocculant pool, causing the positive electrode plate to solidify and form a trapezoidal vertical channel; the flocculant is water.
[0193] Step S6: Drying.
[0194] The dried cathode electrode sheet is obtained by vacuum drying.
[0195] Step S7: Polishing.
[0196] The surface layer produced during the phase inversion process is removed by polishing using Ar ion polishing.
[0197] Step S8: cold pressing.
[0198] The polished positive electrode sheet was rolled to a thickness of 150 μm using a roller pressing system to obtain a positive electrode sheet with a thickness of 313 μm.
[0199] The preparation method corresponding to the comparative example is as follows:
[0200] S1: Slurry preparation.
[0201] Lithium iron phosphate, conductive carbon, and binder polyvinylidene fluoride (PVDF) are weighed in a certain mass ratio, and a certain amount of surfactant additive polyethoxy methacrylate (PMA) is added, dispersed in N-methylpyrrolidone (NMP) solvent, and evenly stirred to form a slurry with good uniformity.
[0202] S2: coating.
[0203] The slurry was adjusted to 0.314 mg / mm 2 The coating weight is double-sided coated on a 13μm aluminum foil substrate to ensure the uniformity of the coating material.
[0204] Step S3: Drying.
[0205] The dried cathode electrode sheet is obtained by vacuum drying.
[0206] Step S4: Cold pressing
[0207] The polished positive electrode sheet was rolled to a thickness of 150 μm on each side using a roller pressing system, resulting in a positive electrode sheet with a thickness of 313 μm.
[0208]
Preparation of negative electrode sheet
[0209] Graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon are added to a certain amount of deionized water, with the mass ratio of graphite: sodium carboxymethyl cellulose: styrene-butadiene rubber: conductive agent being 90:2:3:5, and stirred to form a uniform negative electrode slurry, with the viscosity controlled to be 3000Pa·S~10000mPa·S; the negative electrode slurry is coated on copper foil, and the negative electrode sheet is formed after drying, cold pressing, and slitting.
[0210]
Preparation of electrolyte
[0211] Contains LiPF6, the concentration of which in the electrolyte is 1 mol / L. The solvent includes ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. It also contains fluoroethylene carbonate (FEC), the content of which in the electrolyte is 5wt%.
[0212]
Preparation of isolation film
[0213] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0214]
Preparation of bare battery cells
[0215] The prepared positive electrode sheet, negative electrode sheet and separator are made into corresponding battery cells according to the Z-shaped stacking structure to obtain Figure 8In the battery cell shown, multiple positive electrode sheets 221 and multiple negative electrode sheets 223 are distributed alternately in the order of positive electrode sheet 221, negative electrode sheet 223, positive electrode sheet 221, and negative electrode sheet 223, and the isolation film 222 is folded in a Z-shape and spaced between the positive electrode sheet 221 and the negative electrode sheet 223; the battery cell is vacuum dried at 90°C for 12 hours, and then the positive electrode tab and the negative electrode tab are ultrasonically welded, the positive electrode sheet adopts an aluminum tab, and the negative electrode sheet adopts a nickel tab, and the positive electrode tab and the negative electrode tab are located on the same side of the battery cell.
[0216]
Preparation of lithium-ion batteries
[0217] The battery cell after welding the pole ear is placed in an aluminum-plastic film of suitable size for top-side sealing packaging. The top-side sealing temperature is 145°C. The electrolyte is injected, allowed to stand, formed, aged, exhausted, sealed twice, and capacity tested to obtain the prepared soft-pack laminated battery cell.
[0218] 2. Test Method
[0219] 1. Capillary absorption rate test of positive electrode
[0220] The capillary absorption method is used for testing. The specific process is to place the pre-dried electrode on the microscope stage, use a capillary with a diameter of 0.3mm to absorb 5mm electrolyte, start timing when the capillary contacts the electrode, record the time when the electrolyte is completely absorbed, and finally calculate the capillary absorption rate.
[0221] 2. Liquid absorption test of bare battery cells
[0222] Weigh the dry weight of the bare cell, then soak the bare cell in electrolyte, and weigh the wet weight of the bare cell after immersion at regular intervals. Record the weight of the bare cell before and after immersion, and understand the amount of liquid absorbed by the bare cell based on the change in weight over time.
[0223] 3. Rate performance test of battery cells
[0224] The battery cells were charged at different specified temperatures (-10°C, 0°C, 25°C, 45°C) and charged according to the charging standards of 1 / 6C, 1 / 4C, 1 / 2C, and 1C, and the corresponding charging rates were recorded when charging from the empty state to the specified percentage SOC of the fully charged state (5%, 25%, 50%, 75%, 100%).
[0225] 3. Experimental conditions and test results
[0226] The main experimental conditions in each experimental group are shown in Table 1. For experimental conditions not recorded, please refer to the above records for details and will not be repeated in this article.
[0227] Table 1. Main experimental conditions
[0228]
[0229]
[0230] In Table 1:
[0231] 1) In each embodiment and comparative example, the positions and thicknesses of the designated areas corresponding to the surface, the middle and the bottom are the same, see Figure 6 , the surface refers to the area of the positive electrode active material layer with a thickness of 50 μm starting from the surface away from the positive electrode current collector, the middle refers to the area of the positive electrode active material layer with a thickness of 50 μm centered at the midpoint of the thickness, and the bottom refers to the area of the positive electrode active material layer with a thickness of 50 μm starting from the bottom surface close to the positive electrode current collector;
[0232] 2) The mass proportion of the positive electrode active material refers to the total mass proportion of lithium iron phosphate and magnetic nanoparticles;
[0233] 3) In each of the examples and comparative examples, in the positive electrode active material layer, in addition to the positive electrode active material, the binder and the conductive agent, the balance is the surfactant additive polyethoxy methacrylate (PMA), and the total amount of the four components is 100%.
[0234] According to Table 1, the embodiment satisfies T 外 >T 内 , the ratio does not meet T 外 >T 内 .
[0235] 1. The capillary absorption rate test results are shown in Table 2.
[0236] Table 2. Capillary absorption rate test results
[0237]
[0238] In Table 2, in each embodiment and comparative example, the thickness and area of the five samples are consistent. Among them, the five samples are obtained by cutting the small samples and corresponding to different positions on the surface of the pole piece. Specifically, a sample with a size of 4 cm×4 cm is taken at the center of each folded large surface of the Z-shaped laminate structure, and a total of 5 folded large surfaces are sampled to obtain samples 1 to 5.
[0239] According to Table 2, we can see that:
[0240] Compared with Comparative Example 1, the capillary liquid absorption rate of the positive electrode plate provided in the embodiment of the present application is effectively improved.
[0241] It can be seen from the data in Table 1 that the results are rounded to two decimal places. 表 / T中 =1.12 and T 中 / 底 =1.16, T in Example 3 表 / T 中 =1.08 and T 中 / 底 =1.08, T in Example 4 表 / T 中 =1.18 and T 中 / 底 =1.19. It can be seen that compared with Example 1, Example 3 has a higher T 外 / T 内 The value of is too small, that is, the gradient of the tortuosity is too small; compared with Example 1, Example 4 has a smaller value of T 外 / T 内 The value of is too large, that is, the gradient of the tortuosity is too large. Compared with Example 3, the capillary absorption rate of Example 1 is significantly higher; compared with Example 4, the absorption rates of Example 1 are equivalent.
[0242] Compared with Example 1, Example 5 has a 表 / T 中 =1.24 and T 中 / 底 =1.08, T 表 / T 中 The value of is too high, and the tortuosity of the positive electrode sheet as a whole is too large. Compared with Example 5, Example 1 has a higher capillary absorption rate.
[0243] 2. The corresponding test results of the liquid absorption of the bare battery are as follows Fig. 9 shown.
[0244] according to Fig. 9 It can be seen that the bare cells corresponding to Example 1 and Comparative Example 1 start to absorb liquid with the same dry weight, and the wet weight of the bare cells corresponding to Example 1 after absorbing liquid at the same time is greater, indicating that the bare cells corresponding to Example 1 absorb more liquid. It can be seen that the positive electrode sheet provided in the embodiment of the present application, compared with Comparative Example 1, is effectively improved in liquid absorption when applied to the bare cell.
[0245] 3. The rate performance test results of the battery cells are shown in Table 3.
[0246] Table 3. Rate performance test results
[0247]
[0248] According to Table 3, we can see that:
[0249] Compared with Comparative Example 1, the positive electrode plate provided in the embodiment of the present application has effectively improved rate performance when applied to a battery cell.
[0250] Compared with Example 1, Example 3 has a 外 / T 内 The value of is too small, that is, the gradient of the tortuosity is too small; compared with Example 1, the tortuosity of the positive electrode sheet as a whole is too large in Example 5. Compared with Example 3 and Example 5, Example 1 has better rate performance.
[0251] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode current collector and the positive electrode active material layer are distributed along the thickness direction of the positive electrode sheet; Among them, a plurality of designated areas at different positions in the positive electrode active material layer are selected, and along the thickness direction of the positive electrode sheet, 50 μm ≤ the thickness of the designated area < the thickness of the positive electrode active material layer, and the following conditions are satisfied: among the two designated areas distributed along the thickness direction of the positive electrode sheet, the tortuosity of the designated area on the side away from the positive electrode current collector is T 外 , the tortuosity of the designated area on the side close to the positive electrode current collector is T 内 , T 外 >T 内 .
2. The positive electrode sheet according to claim 1, characterized in that: T 外 / T 内 =1.07~1.24; Optionally, T 外 / T 内 =1.09~1.17; Optionally, T 外 / T 内 =1.09~1.
16.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: Satisfy at least one of the following conditions (a1) to (a3): (a1) The tortuosity of the designated area at the first position is T 表 , the first position is located on a side of the positive electrode active material layer away from the positive electrode current collector, 1.60≤T 表 ≤2.05; optionally, 1.70≤T 表 ≤1.75; (a2) The tortuosity of the designated area at the second position is T 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 1.50≤T 中 ≤1.65; optionally, 1.50≤T 中 ≤1.55; (a3) The tortuosity of the designated area at the third position is T 底 , the third position is located on a side of the positive electrode active material layer close to the positive electrode current collector; 1.30≤T 底 ≤1.55; optionally, 1.30≤T 底 ≤1.
35.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The tortuosity of the entire positive electrode active material layer is T 总 , 1.45≤T 总 ≤1.75; optionally, 1.50≤T 总 ≤1.
70.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The positive electrode active material layer includes a positive electrode active material; in the two designated areas distributed along the thickness direction of the positive electrode sheet, the mass proportion of the positive electrode active material in the designated area on the side away from the positive electrode current collector is C1 外 , the mass proportion of the positive electrode active material in the designated area on the side close to the positive electrode current collector is C1 内 , C1 外 -C1 内 =0.1%~1.2%; Optionally, C1 外 -C1 内 =0.1%~1.0%.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: Satisfy at least one of the following conditions (b1) to (b3): (b1) The mass ratio of the positive electrode active material in the designated area located at the first position is C1 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 97.4%≤C1 表 ≤98.1%; Optionally, 97.4% ≤ C1 表 ≤98.0%; (b2) The mass ratio of the positive electrode active material in the designated area located at the second position is C1 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 96.7% ≤ C1 中 ≤97.3%; Optionally, 97.1% ≤ C1 中 ≤97.2%; (b3) The mass ratio of the positive electrode active material in the designated area located at the third position is C1 底 , the third position is located on a side of the positive electrode active material layer close to the positive electrode current collector; 95.9% ≤ C1 底 ≤96.9%; optionally, 96.4%≤C1 底 ≤96.6%.
7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The positive electrode active material layer includes a binder; in the two designated areas distributed along the thickness direction of the positive electrode sheet, the binder mass ratio of the designated area on the side away from the positive electrode current collector is C2 外 , the mass proportion of the binder in the designated area on the side close to the positive electrode current collector is C2 内 , C2 内 -C2 外 =0.05%~0.8%; Optionally, C2 内 -C2 外 =0.05%~0.45%.
8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: Satisfy at least one of the following conditions (c1) to (c3): (c1) The mass proportion of the adhesive in the designated area located at the first position is C2 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 0.5%≤C2 表 ≤1.0%; optionally, 0.6%≤C2 表 ≤0.9%; (c2) The mass proportion of the adhesive in the designated area at the second position is C2 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 1.0%≤C2 中 ≤1.3%; optionally, 1.0%≤C2 中 ≤1.1%; (c3) The mass proportion of the binder in the designated area at the third position is C2 底 , the third position is located on a side of the positive electrode active material layer close to the positive electrode current collector; 1.3% ≤ C2 底 ≤1.8%; optionally, 1.5%≤C2 底 ≤1.8%; optionally, 1.5%≤C2 底 ≤1.7%.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The positive electrode active material layer includes a conductive agent; in the two designated areas distributed along the thickness direction of the positive electrode sheet, the conductive agent mass ratio of the designated area on the side away from the positive electrode current collector is C3 外 The mass proportion of the conductive agent in the designated area on the side close to the positive electrode current collector is C3 内 , C3 内 -C3 外 =0.2%~0.8%; Optionally, C3 内 -C3 外 =0.2%~0.45%.
10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: Satisfy at least one of the following conditions (c1) to (c3): (c1) The mass proportion of the conductive agent in the designated area located at the first position is C3 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 0.7%≤C3 表 ≤1.4%; optionally, 0.9%≤C3 表 ≤1.4%; optionally, 0.9%≤C3 表 ≤1.2%; (c2) The mass proportion of the conductive agent in the designated area located at the second position is C3 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 1.1%≤C3 中 ≤1.7%; optionally, 1.2%≤C3 中 ≤1.7%; optionally, 1.2%≤C3 中 ≤1.3%; (c3) The mass proportion of the conductive agent in the designated area located at the third position is C3 底 , the third position is located on a side of the positive electrode active material layer close to the positive electrode current collector; 1.2% ≤ C3 底 ≤2.0%; optionally, 1.5%≤C3 底 ≤2.0%; optionally, 1.5%≤C3 底 ≤1.7%.
11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: In the two designated areas distributed along the thickness direction of the positive electrode sheet, the porosity of the designated area on the side away from the positive electrode current collector is P 外 The porosity of the designated area on the side close to the positive electrode current collector is P 内 , P 外 <P 内 ; Optionally, (P 外 / P 内 )×100%=91.4%~96.9%.
12. The positive electrode sheet according to any one of claims 1 to 11, characterized in that: Satisfy at least one of the following conditions (d1) to (d3): (d1) The porosity of the designated area at the first position is P 表 , the first position is located on the side of the positive electrode active material layer away from the positive electrode current collector, 27.5%≤P 表 ≤28.3%; (d2) The porosity of the designated area at the second position is P 中 , the second position passes through the midpoint of the thickness of the positive electrode active material layer, 29.2%≤P 中 ≤30.1%; (d3) The porosity of the designated area at the third position is P 底 , the third position is located on a side of the positive electrode active material layer close to the positive electrode current collector; 30.6%≤P 底 ≤33.3%。 13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: The positive electrode active material in the positive electrode active material layer includes one or more of lithium iron phosphate and modified lithium iron phosphate.
14. A battery, characterized in that: It comprises the positive electrode sheet as claimed in any one of claims 1 to 13.
15. An electrical equipment, characterized in that: Comprising the battery of claim 14.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN113424348A
Lithium-sulfur battery positive plate, preparation method thereof and lithium-sulfur battery
CN115692602A
Positive pole piece, electrochemical device and electric device
CN116504921A
Positive pole piece, preparation method thereof and lithium ion battery
CN119627110A
Electrochemical device and electronic device
WO2022110204A1
Cited By
Electrode plate, preparation method thereof and battery
CN120413604A
An electrode sheet, a method of manufacturing the same, and a battery
CN120413604B